Uji Aktivitas Inhibisi Enzim Tirosinase In-vitro Krim Ekstrak Akar Manis (Glycyrrhiza glabra L.) - Siti Umroh Noor; Faridah Faridah; Pamela Magdalena (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Liquorice root extract (Glycyrrhiza glabra L.) contains glabridin, an isoflavone substance that has the ability to inhibit the oxidation of L-tyrosin and L-DOPA in the formation of melanin, therefore it can be used as skin whitening. The aim of the study was to determine the potential of the best skin whitening cream using positive control of kojic acid. Formulated 1 blank formula, 3 cream formulas using various concentrations of ethanol extract 70% liquorice roots of (0.01, 0.11, 1.01)% based on the value of tyrosinase inhibition activity in vitro from extracts of (50, 75, 100)%. Spectrophotometric method is used to measure the absorption of dopacrome by a microplate reader which was incubated at 37°C at λ 490 nm for 20 minutes. Oil in water cream was prepared by mixing extract with cream base at a temperature of 70-75°C at a speed of 400 rpm for 25 minutes. Stability test was carried out for 4 weeks at room temperature storage and a temperature of 40°C, evaluated for physical quality. The results of determination of IC50 of kojic acid was 20.88 µg / mL; IC50 of extract variation were (126.75; 1130.90; and 10092.41) µg / mL respectively. Cream has milky white-yellowish color; smell of flowers; soft texture; homogeneous; there is no separation; has type M/A; plastic thixotropic flow properties; has an increasing value including viscosity, spreadability, globule size, and pH, which are respectively (455000-620000)cPs, (2695.82-3545.83)mm2, (54.66-66.27)μm , and (4.44-5.04); tyrosinase inhibition activity in formula 1, 2 and 3 were stored at weeks 0, 2nd and 4th were respectively (1.78; -25.74; 22.04)%, (6.74; 6, 12; 4.49)%, and (-28.78; 53.06; 20.32)%. It can be concluded that the cream formula containing liquorice root extract with a concentration of 1.01% is the best formula so it can be used as skin whitening.